The Neo-Solitary Island: A Visual Inquiry Into 文化错位(Cultural Dislocation) Using 梦核(Dreamcore) Collage - Xing, Jiyuan (Auckland University of Technology, 2026)
This practice-based research investigates how the visual strategy of Chinese 梦核(dreamcore) aesthetics can be applied through collage video to express the identity crisis and 文化错位(cultural dislocation) experienced by Chinese international students. It asks: How might Chinese 梦核(dreamcore) aesthetics be used in collage video to express the identity crisis and 文化错位(cultural dislocation) experienced by a Chinese international student in a foreign cultural context? Rooted in my personal experiences as a Chinese student living abroad, the project consists of a series of short experimental videos constructed through collage-based methods. These works draw upon symbolic objects, fragmented memories, and observations from everyday life. In creating the work, I employ a distinctly subjective visual language. Rejecting traditional narrative structures, the work embraces symbolic metaphors to evoke emotional resonance and visual intensity. The merging of personal memory, cultural imagery and aesthetic codes speaks to states of consciousness through edited video composition, where familiar yet uncanny places and people are juxtaposed to elicit feelings of nostalgia, anemoia[ Feelings of nostalgia for a time that one has never experienced (Koenig, 2021).] or confusion. In so doing, the project critically examines the psychological and cultural tension inherent in dislocated identity. This research contributes to the field of moving image practice by offering a non-linear, symbol-driven mode of expression of diasporic experience, while expanding the conceptual and aesthetic potential of collage video through a uniquely Chinese lens.